Microcrystalline cellulose as an effective crystal growth inhibitor for the ternary Ibrutinib formulation. (1st February 2020) - Zhang, Man; Suo, Zili; Peng, Xu; Gan, Na; Zhao, Ludan; Tang, Peixiao; Wei, Xin; Li, Hui
Graphical abstract: Highlights: Different IBR formulations were prepared by mechanochemical methods. MCC is an effective crystal growth inhibitor for the ternary IBR formulation. The biosafety of the ternary formulation was the same as that of IBR. The ternary IBR-OXA-MCC formulation enhances the oral bioavailability of IBR. Abstract: The objective of present study is to explore whether polysaccharide could be a crystal growth inhibitor in poorly soluble antitumor drug Ibrutinib (IBR) formulation. In this work, small molecular ligands (amino or organic acids) in co-amorphous system (CAS) were preliminarily screened. A polysaccharide, microcrystalline cellulose (MCC) was selected to stabilize amorphous drug and enhance pharmacokinetic properties. Fourier-transform infrared, Raman, and X-ray photoelectron spectroscopy confirmed the ionic interaction of the ternary IBR formulation. Moreover, the biosafety of the ternary formulation was the same as that of IBR while the in vitro performance advantage of the ternary formulation was converted into higher bioavailability in vivo experiments. Overall, MCC as an effective crystal growth inhibitor in the novel ternary IBR formulation is a promising approach to improve the dissolution rate of crystalline drugs and the stability of amorphous drugs, as well as providing a theoretical basis for clinical applications.